Morphometrics of the Tropical Bed Bug (Hemiptera: Cimicidae) From Cape Coast, Ghana. Issue 5 (15th June 2022) - Deku, Godwin; Combey, Rofela; Doggett, Stephen L
Abstract: Bed bugs, Cimex lectularius (L.) (Hemiptera: Cimicidae) and Cimex hemipterus (F.), have become established worldwide in recent years largely due to the development of insecticide resistance. However, limited attention has been given to ongoing morphological and macroevolutionary changes within the species and their populations, which could have implications for their control. Here, we evaluated whether bed bugs of the species C. hemipterus inhabiting different communities in Cape Coast, Ghana are undergoing segregation, which could lead to possible speciation. We also aimed to provide a morphometric description of all nymphal stages. Nine-bed bug populations of C. hemipterus were field-collected in Cape Coast and were subjected to geometric morphometric analysis. The multivariate parameters applied distinguished various populations from each of the locations, indicating the presence of morphologically distinct subpopulations of C. hemipterus . Shape-based segregation and shape changes associated with the insect pronotum (which is an important taxonomic character in the Cimicidae) were evident across the populations. Through this comparative study of C. hemipterus, we showed that possible subpopulations of this bed bug are being spread from Ghana. The nymphal stages (first–fifth) of C. hemipterus were distinguished by the length of the last three antennal segment and pronota width; such information contributes to the taxonomic knowledge of the species.